The Effects of Sodium Metabisulfite on the Hippocampus and Prefrontal Cortex in Wistar Rats: A Cognitive, Neurochemical, and Histological Study - Nathaniel Ohiemi Amedu; Patrick Abolarin; Favour Wilcox; Habeeb Abdur-Rahman (Pharmaceutical and Biomedical Research, 2024)
Background: This study investigates the potential effect of sub-chronic exposure to sodium metabisulfite (NaMBS) on the hippocampus and prefrontal cortex of female Wistar rats. Methods: A total of 24 adolescent female Wistar rats were randomly divided into four groups (6 rats each) as follows: Group 1 (control) received 0.5 mL of normal saline; group 2 was administered by 100 mg/kg of NaMBS; group 3 was issued by 300 mg/kg of NaMBS; group 4 received 500 mg/kg of NaMBS. The route of administration was oral for 28 days. After completing the administration phase, the Y-maze test was conducted. Subsequently, the rats were euthanized, and tissue samples from the prefrontal cortex and hippocampus were collected for biochemical assays, precisely measuring malondialdehyde (MDA) and acetylcholinesterase (AChE) levels, as well as histological studies, such as hematoxylin and eosin, and glial fibrillary acidic protein (GFAP). Meanwhile, the neuronal count was done. Results: The learning and memory functions of rats in the treated and control groups were similar (number of alternations: P>0.05). The group treated with 500 mg/kg NaMBS presented indications of neurodegeneration in CA1 of the hippocampus and high glial fibrillary acidic protein-immunoreactivity but had no noticeable effects on layer II/III of the prefrontal cortex. Regardless of the dosage of NaMBS, malondialdehyde level was the same (P>0.05) for all groups; however, in the group that received 500 mg/kg NaMBS, the acetylcholinesterase level was significantly reduced (P˂0.05). Conclusion: This study revealed that while NaMBS can lead to neurodegeneration in the hippocampus of Wistar rats at 500 mg/kg, the prefrontal cortex remains resilient and spatial memory is unaffected, but a decrease in acetylcholinesterase activity raises cognitive concerns, emphasizing the need for cautious consideration of its use.